Raising the Academic Authority of Clinical Experience: The Department of Internal Medicine at Keijo Imperial University and Its Periodical Imsangnaegwahak - Jiyoung PARK (Uisahak, 2024)
This paper examines the periodical Clinical Internal Medicine published by the Department of Internal Medicine at Keijo Imperial University in colonial Korea. Previous studies on medical research at Keijo Imperial University have primarily focused on preclinical departments such as anatomy, hygiene, pharmacology, and microbiology which produced knowledge that supported Japan’s imperialistic expansion. This approach has overlooked the research contributions of clinical departments, often viewing the roles of preclinical and clinical departments through a dichotomy between research versus clinician training. However, Clinical Internal Medicine demonstrates that the Department of Internal Medicine at Keijo Imperial University was actively engaged in research. By analyzing the purpose and content of Clinical Internal Medicine, this paper reveals that its publication was an effort by the Department of Internal Medicine to address the demand for practical knowledge among clinicians practicing outside the university. At the same time, it reflects a commitment to enhancing the academic value of clinical experience and critiques the blind pursuit of experimental medicine in the Japanese medical community in the 1920s and 1930s. The case of the Department of Internal Medicine at Keijo Imperial University illustrates the transformation of clinical experience into “worthy” academic knowledge in colonial Korea. Based on these findings, this paper provides insights into the role of clinical departments at Keijo Imperial University in research and post-graduation education.